Challenges Special Education Teachers Encounter in Using Artificial Intelligence ‎Techniques to Teach Students with Disabilities in Inclusive Schools - Mohammad A. Beirat; Ahmad S. Algolaylat; Alaa K. Al-Makhzoomy (دراسات: العلوم التربوية)
Objectives: This study aimed to identify the challenges special education teachers face when employing artificial intelligence (AI) techniques to teach students with disabilities in inclusive schools in Jordan, and to examine the relationship between these challenges and selected variables.